Determination of the Critical CTAB Concentration for the Carbon-supported CoB Catalysts Synthesis Toward Hydrogen Generation from NABH4 - Hazal Ozdemir, Juelide; Aktas, Baris; Sirin, Ayseguel; Kaan Ozdemir, Oguz (WILEY-V C H VERLAG GMBH, 2025)
Hydrogen production from sodium borohydride (NaBH4) is an inherently slow reaction, necessitating a catalyst to accelerate the process by lowering the activation energy. Cobalt (Co)-based catalysts have gained significant attention due to their affordability and high catalytic performance. However, despite their superior activity, agglomeration can hinder the catalytic efficiency of Co-based materials during reduction, attributed to their high surface energy and magnetic properties, ultimately leading to a lower hydrogen generation rate (HGR). In this study, the effect of cyclohexyl trimethyl ammonium bromide (CTAB), a cationic surfactant, in promoting the homogeneous dispersion of cobalt-boride (CoB) on a carbon support was investigated, and the critical CTAB concentration for the synthesis of carbon-supported CoB toward hydrogen generation from NaBH4 was determined. Comprehensive characterization was performed, including HGR measurements, kinetic analysis, reusability and durability assessments, and physical characterization techniques. The results demonstrate that the addition of CTAB up to an optimal concentration (100 mu L) enhances the HGR by approximately 70%, while exceeding this critical amount adversely affects and decreases the rate. Notably, the highest HGR achieved for the CoB/C-100CTAB catalyst was 37.34 (LH2/min*gcatalyst), and the resultant activation energy for the reaction was determined to be 56 (kJ*mol-1).
Keywords: Cobalt-boride catalysts; Cyclohexyl trimethyl ammonium bromide (CTAB); Hydrogen generation; Sodium borohydride; Surfactant; SODIUM-BOROHYDRIDE HYDROLYSIS; MEMBRANE FUEL-CELLS; B CATALYSTS; NANOPARTICLE CATALYSTS; ASSISTED SYNTHESIS; BORIDE CATALYSTS; OPTIMIZATION; ENERGY; PERFORMANCE; PARTICLES; Chemistry